2005
DOI: 10.1002/marc.200400667
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of a Single Electrospun Fiber and Its Structures

Abstract: Summary: A method to measure the Young's modulus of a single electrospun polyacrylonitrile (PAN) fiber is reported. The Young's modulus can be calculated from the force‐displacement curves obtained by the bending of a single fiber attached to an atomic force microscopy (AFM) cantilever. It is suggested that the high modulus of electrospun fibers is caused by the orientation of molecular chains, which is confirmed by wide‐angle X‐ray diffraction (WAXD) measurements. The communication will provide a basic unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 26 publications
2
100
0
3
Order By: Relevance
“…12 Furthermore, such local measurements do not provide input about the dominant mode of deformation and failure of nanofibers in their expected application which is axial stretching. Three-point-bending 12,13 and cantilever bending 14 tests on nanofibers and nanowires have also been reported. These measurements may provide a mean to study the linearly elastic response of a fiber 12,13 and its yield point.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, such local measurements do not provide input about the dominant mode of deformation and failure of nanofibers in their expected application which is axial stretching. Three-point-bending 12,13 and cantilever bending 14 tests on nanofibers and nanowires have also been reported. These measurements may provide a mean to study the linearly elastic response of a fiber 12,13 and its yield point.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, the difference is enormous and surprising. [3][4][5] For example, Gu et al 4 reported a Young's modulus of 50 GPa for polyacrylonitrile single nanofibers, which is much greater than that of the corresponding cast film (1.2 GPa). Kim et al 5 observed the phenomenon of "necking" with poly(methyl methacrylate) (PMMA)/montmorillonite nanocomposite electrospun single fibers, whereas PMMA is known as a brittle plastic.…”
mentioning
confidence: 99%
“…Figure 8 shows the typical stress-strain curves of pure PMMA (a) and the PMMA/ACNs nanocomposites (b). The tensile strength, the tensile modulus and the strain at break values are summarized in [27,28]. The aspect ratio of MWNTs was 15, using measurements from transmission electron microscopy images.…”
Section: Resultsmentioning
confidence: 99%